Food habits of school pupils in Tromsø, Norway, in the transition from 13 to 15 years of age - Øvrebø, Else Marie (International Journal of Consumer Studies, 2011)
The aim of this study was to investigate the development of food habits in adolescents in Tromsø, whether pupil behaviour regarding food habits had changed in grade 10 compared to grade eight, and whether this was linked to pupils` Home Economics lessons in grade nine. A total of 606 adolescents (321 boys and 285 girls) were studied on two different occasions – 2002 and 2005, A food-frequency questionnaire comprising 16 different food and beverage groups was used. The questionnaire also enquired about food habits, the amounts consumed of some food items and the socioeconomic conditions of the participants and their families. The frequency of eating breakfast, lunch and dinner reduced from 8th to 10th grade. No significant differences were found between 8th and 10th graders in their frequency of consuming fruit and vegetables. Tenth graders ate chocolate and snacks more often than 8th graders. Girls reported eating fruit and vegetables more often than boys. This applies to both 8th and 10th graders. Far more pupils from both groups need to eat more fruit and vegetables every day. The conclusion of the study is that food habits change significantly from the 8th to the 10th grade. Further progress must be achieved in addressing the issue of translating the theory of nutritional education into practice. More studies and evidence are required to understand the potential of the Home Economics curricula to change the unhealthy eating trends seen in this and other studies.